Should Adrenal Venous Sampling Be Performed in PA Patients Without Apparent Adrenal Tumors? - Okamoto, Kentaro; Ohno, Youichi; Sone, Masakatsu; Inagaki, Nobuya; Ichijo, Takamasa; Yoneda, Takashi; Tsuiki, Mika; Wada, Norio; Oki, Kenji; Tamura, Kouichi; Kobayashi, Hiroki; Izawa, Shoichiro; et al. (Frontiers in Endocrinology, 2021)
Introduction: Some aldosterone-producing micro-adenomas cannot be detected through image inspection. Therefore, adrenal venous sampling (AVS) is often performed, even in primary aldosteronism (PA) patients who have no apparent adrenal tumors (ATs) on imaging. In most of these cases, however, the PA is bilateral. Objective: To clarify the clinical need for AVS in PA patients without apparent ATs, taking into consideration the rates of adrenalectomy and cardiovascular disease (CVD) among these patients. Methods: This is a retrospective cross-sectional study assessing 1586 PA patients without apparent ATs in the multicenter Japan PA study (JPAS). We analyzed which parameters could be used to distinguish unilateral PA patients without apparent ATs from bilateral patients. We also analyzed the prevalences of CVD and adrenalectomy in unilateral PA patients. Results: The unilateral subtype without an apparent AT was diagnosed in 200 (12.6%) of 1586 PA patients. Being young and female with a short hypertension duration, normokalemia, low creatinine level, low plasma aldosterone concentration, and low aldosterone-to-renin ratio (ARR) was significantly more common in bilateral than unilateral PA patients. If PA patients without apparent ATs were female and normokalemic with a low ARR (<560 pg/ml per ng/ml/h), the rate of unilateral PA was only 5 (1.1%) out of 444. Moreover, among the abovementioned 200 patients, the rate of a history of CVD was 19 out of 143 (13.3%) in males but only 1 out of 57 (1.8%) in females. In addition, 77 of the 200 (38.5%) did not receive adrenalectomy, despite being diagnosed with the unilateral subtype based on AVS. Conclusion: The low prevalence of the unilateral subtype in PA patients without apparent ATs suggests AVS is not indicated for all of these patients. AVS could be skipped in female normokalemic PA patients without apparent ATs if their ARRs are not high. However, AVS should be considered for male hypokalemic PA patients with high ARRs because the rates of the unilateral subtype and CVD are high in these patients.